The Influence of the Indonesian Zakat Initiative Institution (IZI) in Improving the Economy of the Poor Community in Makassar - Awalia, Ananda Khadijah; Aisyah, Siti; Abdi, Muhammad Nur (Dinasti International Journal of Management Science, 2025)
This study This study aims to determine how much influence the Indonesian Zakat Initiative Institution (IZI) has in improving the economy of the poor in Makassar. The population in this study is the Community. Sampling using the Slovin formula as many as 45 respondents. The type of data used in this study is quantitative which is obtained from the questionnaire distributed to respondents. Based on the results of the study using statistical calculations through the SPSS version application. regarding the influence of the Indonesian Zakat Initiative Institution (IZI) in improving the economy of the poor in Makassar has a positive and significant effect on improving the economy of the poor in Makassar.